Problem dan Solusi Pengembangan Perbankan Syariah Kontemporer di Indonesia - Subandi Subandi (AL-TAHRIR, 2012)
Contemporary development of the national banking today is being a serious international spotlight. Since national economic crisis, the national banking is often unable to compete with foreign banks in Indonesia. On its symptoms, a national banking customers are coming from an average of lower middle class. This condition was not even able to raise the welfare of Indonesian people to be better life to just get out of the shackles of ‘poverty’. Especially Islamic banking in Indonesia, the beginning of its presence is expected to be the main solution to the problem of poverty in this state, but it also can not do much. It refers to data from Bank Indonesia, the Islamic banking business unit transactions in Indonesia in 2008 has increased to Rp. 24 trillion that is equivalent to 1.8 percent. But in fact, it is just superficial, because it is basically only able to contribute at 2:98, when compared with conventional banking. The large gap that happened is caused by three main issues: the legality aspects, human resources aspects, and aspects of less innovative marketing strategies. To solve the problems needs some strategies namely; improving the quality of service and professionalism, products innovation, qualified human resources, etc.